Publication Trend of Public Sentiment Towards Indonesia Government Policies - Permana, Iip; Maani, Karjuni Dt (Politeknik Ganesha Medan, 2024)
There are 167 million social media users in Indonesia. Some of these users express their opinions on social media known as public opinion. Public sentiment is the classification of public opinion into several classes. Understanding public sentiment through some public policies can benefit the government. Publication trends can be a stepping stone to deeply understanding a research topic. No research was conducted on the publication trend of public sentiment toward Indonesian government policies on social media. This study aims to explore publication trends in the area of public sentiment toward Indonesia government policies on social media using bibliometric analysis. The Scopus database is used to gather abstracts and keywords, funding details, citation information, bibliographical information, and other information. Search document terms used are